REPRESENTASI ISU PLURALISME DALAM FILM TANDA TANYA - Nawidiya, Ni Putu Sanisa; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT Pluralism comes from the word plural and isn, plural which means plural, whereas isn means to understand. The Question Mark tells about religious pluralism in Indonesia. Where conflicts between religions have become common, and a long history of violence and discrimination against Chinese in Indonesia. This film tells about three families who live in a village, in Semarang, Central Java. The purpose of this research is to find out the representation of the plurarism issues of the Indonesian people who are contained in the Question Mark Film. Based on the analysis of the related scenes using the semiotic method of Charles S. Peirce in the film, it shows that pluralism in the film Question Mark occurs in the daily lives of the community life Semarang. This study concluded that the Question Mark Film presented acts of pluralism that emerged in the form of dialogue, and behavior. Keywords: Representation, Pluralism, Tolerance, Semiotics.